A genome-wide association study of suicide severity scores in bipolar disorder. (June 2015) - Zai, Clement C.; Gonçalves, Vanessa F.; Tiwari, Arun K.; Gagliano, Sarah A.; Hosang, Georgina; de Luca, Vincenzo; Shaikh, Sajid A.; King, Nicole; Chen, Qian; Xu, Wei; Strauss, John; Breen, Gerome; et al.
Abstract: Background: Suicide claims one million lives worldwide annually, making it a serious public health concern. The risk for suicidal behaviour can be partly explained by genetic factors, as suggested by twin and family studies (reviewed in (Zai et al. 2012)). Recently, genome-wide association studies (GWASs) of suicide attempt on large samples of bipolar disorder (BD) patients from multiple sites have identified a number of novel candidate genes. GWASs of suicide behaviour severity, from suicidal ideation to serious suicide attempt, have not been reported for BD. Methods: We conducted a GWAS of suicide behaviour severity in three independent BD samples:212 small nuclear families with BD probands from Toronto, Canada, 428 BD cases from Toronto, and 483 BD cases from the UK. We carried out imputation with 1000 Genome Project data as reference using IMPUTE2. Quality control and data analysis was conducted using PLINK and R. We conducted the quantitative analyses of suicide behaviour severity in the three samples separately, and derived an overall significance by a meta-analysis using the METAL software. Results: We did not find genome-wide significant association of any tested markers in any of the BD samples, but we found a number of suggestive associations, including regions on chromosomes 8 and 10 ( p < 1e-5). Conclusions: Our GWAS findings suggest that likely many gene variants of small effects contribute collectively to the risk for suicidal behaviour severity in BD. Larger independent replications are required to strengthen the findings from the GWAS presented here. Highlights: We performed a genome-wide association study (GWAS) of suicide behaviour severity. Our GWAS was conducted in three samples of bipolar disorder patients. Suggestive associations were found in chromosomes 8p23-p24 and 10p11.